The effects of genetic bottlenecks on mutation fixation and replicative capacity of the influenza A virus - Mamerow, Michael (My University, 2018)
The influenza A virus is a common cause of respiratory illness in humans. Seasonal epidemics of influenza in the United States can result in up to 40 million cases, with annual hospitalizations and deaths reaching as high as 400,000 and 70,000, respectively. The influenza A virus continually causes annual epidemics, despite yearly vaccines, as a result of its high mutation rate, leading to genetically diverse viral populations within hosts. Respiratory droplet-mediated transmission of the virus between individuals is accompanied by a bottleneck event that decreases the diversity of the viral population passed to new hosts. Using controlled artificial bottlenecks of different sizes during in vitro serial passaging, the impact of these bottleneck events on patterns of mutation fixation and replicative capacity of the influenza A virus was determined. Growth curves and genome sequencing were used after passaging to characterize differences in replicative capacity and identify genomic changes within the population. Serial passaging at a bottleneck size of one virus generated virus populations with lower replicative capacity as compared to the original parental virus. This effect was associated with fixation of numerous mutations spread throughout the genome. An increase in replicative capacity was evident after repeated bottlenecks of 1000 viruses, demonstrating that sufficiently loose bottlenecks do not compromise viral replication kinetics and even allow for improvement. This increase in replicative capacity was associated with several mutations, clustered primarily in the hemagglutinin genome segment.
Keywords: Microbiology; Avian Influenza Viruses; Mutation